2022
DOI: 10.1007/s10461-022-03943-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pre-exposure Prophylaxis (PrEP) Implementation in Transgender Populations: A Qualitative Scoping Review

Abstract: We conducted a scoping review of contextual factors impeding uptake and adherence to pre-exposure prophylaxis in transgender communities as an in-depth analysis of the transgender population within a previously published systematic review. Using a machine learning screening process, title and abstract screening, and full-text review, the initial systematic review identified 353 articles for analysis. These articles were peer-reviewed, implementation-related studies of PrEP in the U.S. published after 2000. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Finally, the ability to decrease the frequency of PrEPrelated visits to every 6 months was strongly preferred among all respondents regardless of PrEP status. Several next-generation PrEP modalities under development may be amenable to this preference [13,60,62,80]. Future studies should be more inclusive and enrol more substantial numbers of trans participants to obtain more reliable findings related to product efficacy, acceptability and implementation opportunities among this priority population.…”
Section: Table 2 Results Of Choice-based Conjoint Analysis Experiment...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the ability to decrease the frequency of PrEPrelated visits to every 6 months was strongly preferred among all respondents regardless of PrEP status. Several next-generation PrEP modalities under development may be amenable to this preference [13,60,62,80]. Future studies should be more inclusive and enrol more substantial numbers of trans participants to obtain more reliable findings related to product efficacy, acceptability and implementation opportunities among this priority population.…”
Section: Table 2 Results Of Choice-based Conjoint Analysis Experiment...mentioning
confidence: 99%
“…In light of these recommendations, tailored implementation strategies to achieve equitable PrEP delivery for trans populations are needed [3,13]. Regrettably, implementation studies rarely enrol trans participants in numbers sufficient to yield reliable estimates-transfeminine participants are often subsumed into study cohorts comprised predominantly of cisgender sexual minority men, while transmasculine and nonbinary individuals are rarely enrolled at all [13][14][15][16][17][18] Limited inclusion of trans participants in implementation research will hinder efforts to develop strategies that are salient and relevant to trans individuals who might otherwise benefit from PrEP due to their current sexual practices or personalized HIV prevention needs and preferences [3,13,15,19]. However, prior research with trans participants across other fields of research may inform this work.…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Table 1 , studies with TGW demonstrated the relevance of various factors on PrEP use that can be mapped in the COM-B. Factors related to the capability domain include HIV prevention knowledge, and skills; factors related to opportunity dimensions include societal influences, resources, interactions with healthcare systems, family, and peers, and HIV stigma; and motivational factors include beliefs, intentions, concerns, mental health states, and habits [ 8 , 9 , 20 , 21 ]. The COM-B relies on the delineation of explanatory factors that influence a particular behaviour on multiple levels [i.e., individual, interpersonal, and contextual], which helps us to identify barriers and facilitators, and a structured framework for intervention design [Objective 1].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, major biomedical advancements such as pre-exposure prophylaxis (PrEP), have proven to be very effective at preventing HIV. Yet many of these interventions have not been widely implemented with equity to yield their intended bene t. Only an estimated 30% of individuals who would bene t from PrEP receive it, with growing disparities by race, gender, income, citizenship status, and intersectional marginalization (11)(12)(13)(14). Uptake and adherence remain suboptimal along the HIV care continuum (i.e., prevention, testing, diagnosis, linkage-to-care, and treatment), indicating, in part, failed implementation and opportunities to develop evidence-informed implementation strategies (11).…”
Section: Hiv and Implementation Researchmentioning
confidence: 99%